SROI with Assurance Can Help Contributors Distinguish Hypocritical Organizations from Genuine NFPs - Fuminobu Mizutani (Emerging Science Journal, 2021)
The American film Poverty, Inc. alerted citizens to the fact that some “not-for-profit” organizations impair public benefit and seek profit. To avoid to contributing to such hypocritical organizations, this paper considers the possible use of SROI. SROI is an accounting concept used to evaluate NFPs. There is a problem called overhead aversion among contributors. It is hypothesized that spreading the use of assurance on SROI will face this problem. If so, a measure against this is necessary. This paper builds its theory on the existence of negative SROI as a tool to distinguish hypocritical organizations from genuine NFPs from the perspective of welfare economics, and argues that, theoretically, SROI can be negative. This paper then uses a questionnaire-based survey and conducts various statistical analysis to show that disclosure of SROI with assurance is practical. Nevertheless, it is also shown that assurance on SROI faces overhead aversion, a measure against which is provided by an influential paper. Spreading the use of SROI with assurance will trigger a shift from contribution to hypocritical organizations to contributions toward genuine NFPs. Such a shifts in contributions may also improve welfare. The main conclusion of this paper is that SROI with assurance can help contributors distinguish hypocritical organizations from genuine NFPs. Doi: 10.28991/esj-2021-01253 Full Text: PDF